Lake Chad Regional Economic Memorandum : Development for Peace - Granguillhome, Rogelio; Hernandez, Marco; Lach, Samantha; Masaki, Takaaki; Rodríguez-Castelán, Carlos (World Bank, Washington, DC, 2021)
This report sheds light on the interlocked long-term territorial development challenges and the recently realized systemic risks affecting the Lake Chad region. It summarizes the findings of seven technical papers, each investigating different aspects of the interlinked challenges faced by the region. These studies are accompanied by complementary research on labor market and geospatial socioeconomic trends, as well as by a review of the thin literature on economic development across the region. In addition to presenting the main results of the technical papers, the report positions the findings in the broader context of an analytical framework depicting the feedback mechanisms between the region’s territorial development gaps and the self-reinforcing link to shocks, namely, violent conflict and climate change. This analytical framework is presented in Section 1.2. The rest of the report is structured as follows. Section 1.3 describes the main social and economic trajectories in the region. It reviews long-term demographic trends, suggesting. Section 1.4 argues that the low-growth, high-poverty equilibrium observed in the region is closely linked to the region’s economic geography. Section 1.5 discusses how the impact of climatic variation and violent conflict experienced in the region interlink with and exacerbate the territorial development challenges. Section 1.6 presents policy directions structured around four crosscutting themes: infrastructure, trade, governance, and natural resource management. The crosscutting nature of these themes encourages the exploration of potential synergies across challenge areas. The discussion in the section aims to inform policy-making efforts to strengthen territorial development and mitigate the impacts of conflict and climate change. Such endeavors can increase the likelihood of breaking free from the self-reinforcing negative mechanisms and boost the potential return of the region to a path of stability and inclusive economic development.